Growth of Oil Palm Seedlings on Several Doses of Sugarcane Blotong and Soil Types - Suryanti, Sri; Firmanto, Agung; Rahayu, Enny (Journal TECHNO, 2023)
Blotong is sugar factory waste which can be used as organic fertilizer. Research on the effect of sugarcane doses for several types of soil was carried out with the aim of knowing the effect of blotong doses and soil types on the growth of oil palm seedlings in designpre-nursery. The research was conducted at the Stiper Agricultural Institute Research and Experimental Garden located in Maguwoharjo village, Depok District, Sleman Regency, DIY from March to June 2021. The experimental method used was a completely randomized design with two factors. The irst factor was the blotong dosage which consists of five levels, namely 0, 100, 200, 300 and 400 grams / polybag. The second factor was the type of soil which was divided into three levels, namely latosol, regosol and grumusol. The research data were analyzed using analysis of variance at a real level of 5% and if there were significant differences, it was continued with the Duncan Multiple Range Test. Observations were made on the parameters of seedling height, number of leaves, leaf area, fresh crown weight, shoot dry weight, root fresh weight, root dry weight,  length of primary root, number of primary root, number of secondary root, number of tertiary root and root volume. The results showed that there was no significantly interaction between blotong and soil type on all observed parameters. The use of blotong at a dose of 300 g significantly increased seedling height and primary root length. The use of latosol soil as a seeding medium significantly increased seedling height and fresh shoot weight, while grumusol soil increased the number of secondary and tertiary roots.